A qualitative approach to assessing how the care system can impact on young people - Scott, Kevin B. (2018)
The thesis attempted to explore the 'lived experience' of young people who have been through the care system, in order to ascertain what changes could be implemented to improve the psychological wellbeing of young people going into the care system in the future. After a brief introduction (chapter one), an evidence synthesis (chapter two) on young people who have been in residential care was conducted, to examine this phenomenon from an international perspective. A comprehensive search strategy produced fifteen studies, which were selected for final review. A process of data extraction and subsequent data synthesis of the fifteen studies yielded twelve themes. The developed themes included topics such as, for example, the quality of relationships: between the young people, the young people and the care staff and the wider community. The thesis then used an empirical research piece (chapter three) to narrow the focus of the topic to Ireland and to explore the views of young people in conjunction with the views of care workers. For this purpose, a convenience sample of twenty participants (ten residential care workers and ten young people who had been through residential care), completed a care questionnaire and an open-ended interview of one-hour duration. A thematic analysis was performed to comprehend the raw data. The thematic analysis of the dataset elicited fourteen themes; 2 young person themes, 3 care worker themes, and 9 joint themes. The developed themes addressed areas such as: 'fitting in,' 'what makes a care worker' and 'wider connected processes.' The findings were considered in light of other research literature in this area. Since many of the themes related to psychological wellbeing of young people in the care system, the Trauma Symptoms Checklist for Children - Alternate (TSCC-A) was chosen as a psychometric to be critiqued (chapter four). The: properties, normative data, reliability, validity and applicability of the measure were considered. In terms of applicability, how appropriate the measure is for use with young people in the care system was a salient issue. The TSCC-A was used to then assess levels of trauma and psychological wellbeing with the young person in the case study (chapter five). In contrast to the earlier chapters, chapter five looked at the care system in terms of secure institutional care (as opposed to residential care in the earlier chapters), which produced insights into the care establishment as a whole and emphasised aspects such as the importance of therapeutic milieu. D4 who was diagnosed with schizophrenia and committed acts of criminal damage and arson had an individualised care approach adopted with him. He was given pre and post psychometrics to chart the success of his time in care (pre and post intervention). The findings suggested that D4 had shown improvement towards his propensity for negative internalising and externalising behaviours and his psychological wellbeing overall had improved. Chapter six then attempted to consider many of the different insights offered by the preceding chapters and it ends by offering suggestions for how the psychological wellbeing for young people in the care system could be improved, through the amelioration of treatment integrity.